2023
DOI: 10.1038/s41380-022-01933-9
|View full text |Cite
|
Sign up to set email alerts
|

Volume of subcortical brain regions in social anxiety disorder: mega-analytic results from 37 samples in the ENIGMA-Anxiety Working Group

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
5
1
Order By: Relevance
“…A recent mega-analytic study using 37 samples consisting of 1115 individuals with SAD and 2775 HCs was conducted by ENIGMA-Anxiety. This study found smaller amygdala volumes in SAD individuals with comorbid anxiety disorder and comorbid MDD 13 . Additionally, given that the amygdala and hippocampus consist of structurally heterogenous units of specialized subfields that can be identified by their cytoarchitecture, histochemistry and connectivity profile 14 , it is likely that investigating the volume of the amygdala and hippocampal as whole structures might not reveal subfield specific differences that may occur in SAD.…”
Section: Introductionsupporting
confidence: 45%
“…A recent mega-analytic study using 37 samples consisting of 1115 individuals with SAD and 2775 HCs was conducted by ENIGMA-Anxiety. This study found smaller amygdala volumes in SAD individuals with comorbid anxiety disorder and comorbid MDD 13 . Additionally, given that the amygdala and hippocampus consist of structurally heterogenous units of specialized subfields that can be identified by their cytoarchitecture, histochemistry and connectivity profile 14 , it is likely that investigating the volume of the amygdala and hippocampal as whole structures might not reveal subfield specific differences that may occur in SAD.…”
Section: Introductionsupporting
confidence: 45%
“…Remarkably, reduced putamen grey matter volume was the only significant main effect of group (SAD vs. HC) in subcortical areas in a recent study with 1,115 SAD patients and 2,775 controls [77]. In one study, social anxiety severity was positively correlated with putamen volume [76], but this effect was later questioned [77]. Regarding functional activity, a number of studies have reported altered putamen activations in SAD patients in response to both socially positive and negative stimuli [4, 7, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Altered putamen structure and activity have been associated with the diagnosis of SAD in several previous studies. Structural studies revealed altered grey matter volumes in the putamen in SAD patients relative to HC [e.g., [76][77][78][79]]. Remarkably, reduced putamen grey matter volume was the only significant main effect of group (SAD vs. HC) in subcortical areas in a recent study with 1,115 SAD patients and 2,775 controls [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genetically informed findings are consistent with previous observational studies. For example, increased bilateral pallidum volumes were found to be associated with social anxiety disorder (SAD) in adults (44). Furthermore, negative covariation between salivary cortisol during public speaking and regional cerebral blood flow in Brodmann area 6 was reported in SAD patients (45).…”
Section: Discussionmentioning
confidence: 99%